THE DEVELOPMENT OF FEMINIST EPISTEMOLOGY IN ISLAMIC STUDIES IN INDONESIAN UNIVERSITYA: Case Study of Akhwal Syaikhsiyah Study Program of Darussalam Islamic Institute, Ciamis West Java - Sumadi, S (EpistemÃƒÂ©: Jurnal Pengembangan Ilmu Keislaman, 2017)
The main issue to be discussed in this study is the development of epistemology in feminist perspective in the academic context. Gender bias still dominates in Islamic study. Ahwal Syaikhsiyah study program or also known as Islamic Family law study program in Indonesia is closely related to internalization of gender equality values. The subjects in this study programare related to family and relations in the family according to Islamic Law. Therefore, the development of feminist epistemology in Ahwal Syaikhsiyah study program is inevitable in Indonesia. Some of the development is performed by Ahwal Syaikhsiyah study program of Darussalam Islamic Institute, Ciamis. The development of feminist epistemology starts from developing a curriculum designed with a feminist perspective, learning subjects with feminist perspective and implementation of research model with feminist perspective for lecturers and students. The result, students can respond to the development of feminist epistemology starting from a class lesson, critical analysis on issues based on misogynistic Islamic perspective which marginalizes, subordinates, and contains elements of violence against women. The analysis result of various problems of the relation between gender and Islam in the study of Ahwal Syaikhsiyah was studied in this research. The students who focused on theÂ study of relation in the family used feminist perspective as an analysis tool in undergraduate theses. However, for lecturers, feminist perspective wasnât used as perspective in research. The development of feminist epistemology can be a systematic way in creating a women-friendly academic atmosphere which supports gender equality and equity.Masalah pokok yang dibahas dalam kajian ini adalah pengembangan epistemologi berperspektif feminis dalam ranah akademis. Di Indonesia bias gender masih mendominasi kajian Islam. Program Studi Ahwal Syaikhsiyah atau yang disebut dengan Program Studi Hukum Keluarga Islam, di Indonesia termasuk yang memiliki keeratan dengan internalisasi nila-nilai kesetaraan gender. Sebab pada program studi ini mata kuliahnya terkait relasi-relasi dalam keluarga menurut hukum Islam. Oleh karena itu pengembangan epistemologi feminis pada program studi Ahwal Syaikhsiyah menjadi keniscayaan di Institut Agama Islam Darussalam Ciamis. Pengembangan epistemologi feminis diawali dari pengembangan kurikulum yang dirancang dengan perspektif feminis, pembelajaran matakuliah dengan perspektif feminis, dan penerapan model penelitian dengan perspektif feminis bagi dosen dan mahasiswa. Hasilnya, untuk para mahasiswa dapat merespon pengembangan epistemologi feminis dari mulai pembelajaran di kelas, analisis kritis pada masalah-masalah yang didasari oleh perspektif Islam yang misoginis, memarjinalkan, mensubordinasi, dan mengandung unsur kekerasan terhadap perempuan. Hasil analisis terhadap berbagai masalah relasi gender dan Islam dalam kajian Ahwal Syaikhsiyah dijadikan sebagai masalah yang dikaji dalam bentuk penelitian. Para mahasiswa yang memfokuskan pada kajian relasi dalam keluarga menjadikan perspektif feminis sebagai alat analisis dalam penelitian-penelitian dalam bentuk skripsi. Akan tetapi untuk para dosen, perspektif feminis cenderung belum menjadi perspektif dalam penelitian. Pengembangan epistemologi feminis dapat menjadi jalan secara sistematis dalam mewujudkan atmosfir akademik yang ramah perempuan dengan menjunjung kesetaraan dan keadilan gender.